Chemical constituents and antimicroblal activity of two arieties of Etlingera Elatior flowers - Muhamad Azhar, Nurul Iryani (2013)
Etlingera elatior is synonymous with Phaeomeria speciosa, Alpinia elatior, Elettaria speciosa, Nicolaia elatior and Nicolaia speciosa. The species is native to Peninsular Malaysia and Indonesia. In Malaysia, it is called kantan. The essential oil and phytochemicals of two Etlingera elatior flowers varieties (pink and red flower variety) have been studied. The essential oil of the fresh E. elatior flowers was extracted using the hydrodistillation technique and analysed by Kovats Indices and Gas Chromatography-Mass Spectrometry (GC-MS). Hydrodistillation of E. elatior (pink flower variety) flowers gave 70.63% of essential oil classified as monoterpenes, sesquiterpenes, and oxygenated of monoterpenes and sesquiterpenes derivatives. The major constituent identified in the essential oil is cyclodecane (38.07%). Extraction of the dried flowers was done by soxhlet and cold extraction methods using chloroform and dichloromethane, respectively. Fractionation and purification on the crude extracts using Vacuum Liquid Chromatography (VLC) and Column Chromatography (CC) was successfully isolated ß-sitosterol and a mixture of stigmasterol and ß-sitosterol. Their structures were elucidated by GC, GC-MS, IR, 1H NMR and 13C NMR spectroscopies. The antimicrobial activity of essential oil, crude extracts and ß-sitosterol was carried out using disc diffusion method, Minimum Inhibition Concentration (MIC) and Minimum Bactericidal Concentration (MBC) assay with eight strains of bacteria, Enterococcus faecalis, Staphylococcus aureus, Bacillus subtilis, Bacillus cereus (Gram positive), Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumonia and Pseudomonas putida (Gram negative). Antimicrobial screening showed that the essential oil gave moderate to strong inhibition to most of the bacteria with minimum inhibition concentration between 225-900 µg/mL.